2015
DOI: 10.1111/nmo.12710
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain responses in subjects with irritable bowel syndrome during cued and uncued pain expectation

Abstract: Background A majority of subjects with irritable bowel syndrome (IBS) show increased behavioral and brain responses to expected and delivered aversive visceral stimuli during controlled rectal balloon distension, and during palpation of the sigmoid colon. We aimed to determine if altered brain responses to cued and uncued pain expectation are also seen in the context of a noxious somatic pain stimulus applied to the same dermatome as the sigmoid colon. Methods A task-dependent functional magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 87 publications
(197 reference statements)
3
35
0
1
Order By: Relevance
“…These findings are in line with our second hypothesis and support the notion of partially overlapping central mechanisms underlying nocebo effects induced by verbal suggestions and classical conditioning, particularly encompassing cingulate, prefrontal, and somatosensory networks. The contribution of pACC and dlPFC to attention, cognitive appraisal, and top‐down inhibitory control is well established in the broader pain field as well as in visceral pain and IBS . Together with existing work from the somatic pain field, our findings in visceral pain suggest this pain‐modulatory system to be involved across pain modalities.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These findings are in line with our second hypothesis and support the notion of partially overlapping central mechanisms underlying nocebo effects induced by verbal suggestions and classical conditioning, particularly encompassing cingulate, prefrontal, and somatosensory networks. The contribution of pACC and dlPFC to attention, cognitive appraisal, and top‐down inhibitory control is well established in the broader pain field as well as in visceral pain and IBS . Together with existing work from the somatic pain field, our findings in visceral pain suggest this pain‐modulatory system to be involved across pain modalities.…”
Section: Discussionsupporting
confidence: 66%
“…The contribution of pACC and dlPFC to attention, cognitive appraisal, and top-down inhibitory control [40][41][42][43] is well established in the broader pain field 44,45 as well as in visceral pain and IBS. 21,46,47 Together with existing work from the somatic pain field, our findings in visceral pain suggest this pain-modulatory system to be involved across pain modalities.…”
Section: Test Phasesupporting
confidence: 67%
“…Hence, increased attention to interoceptive, visceral sensations may lead to the exacerbation of symptoms and distress (82) in line with the fear avoidance model, which has yet to be more fully tested in the context of chronic visceral pain and the gut-brain axis. Neuroimaging studies support this assumption by demonstrating increased functional connectivity in the salience network in IBS patients during resting state (83), rectal stimulation (84) and contextual threat situations (85). Initial support that the behavioral modification of attentional bias may improve attentional functioning and regulation of brain mechanisms related to anxiety and attention in IBS patients (86,87), provides a treatment perspective to complement more basic mechanistic research.…”
Section: Discussionmentioning
confidence: 95%
“…[52] IBS patients exhibit hyperactivity in the amygdala and connected brain regions both at baseline and in response to visceral stimulation. [53,54] In some studies at least, sex and genetic differences have been identified in IBS-induced amygdala hyperactivity, and stronger effects are observed in males [55] and those with a particular polymorphism of the serotonin receptor gene, HTR3A. [56] Overall, amygdala hyperactivity seems to be related to chronic visceral hypersensitivity, pointing to another important link between the gut and the amygdala.…”
Section: Amygdala Regulates Affective Responses In Pain and Irritablementioning
confidence: 99%